Kajian Hukum Terhadap “Keputusan Tata Usaha Negara (KTUN) Nomor 10/G/2023/PTUN.SMD.” Oleh Pengadilan Tata Usaha Negara (PTUN) Kota Samarinda Atas Penerbitan Surat Pemberhentian Dalam Jabatan - Yanti, Rosida; Paselle, Enos; Kotijah, Siti (Universitas Quality, 2023)
This research aims to examine the legal aspects of State Administrative Court Decision No. 10/G/2023/PTUN.SMD, issued by the State Administrative Court (PTUN) in Samarinda, in response to a case of alleged injustice brought forward by an official from North Kalimantan. The official initially served as the head of the Public Works and Spatial Planning Agency (PUPR-PERKIM) and was subsequently transferred to the Environmental Analyst position within the Department of Natural Resources and Mining and the Environment under the Economic Bureau of the Provincial Secretariat of North Kalimantan. The research employs a juridical-normative methodology, with an approach that involves a thorough examination of legal literature, legislation, and relevant written materials. The study focuses on legal aspects within the administrative process and evaluates the legal effectiveness concerning decisions to terminate an official from their position. The research findings indicate that the legal certainty surrounding a decision to terminate an official's position can be nullified if it complies with the administrative process and is legally invalidated by the PTUN, with final legal force. As a result, the decision is deemed null and void, and the plaintiff is entitled to return to their original position, with significant implications for the official from North Kalimantan.